1998
DOI: 10.2136/sssaj1998.03615995006200020008x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sorption of Imidacloprid with Incubation Time

Abstract: Changes in sorption of the insecticide imidacloprid (1‐[(6‐chloro‐3‐pyridinyl)‐methyl]‐N‐nitro‐2‐imidazolidinimine) with aging in three soils have been determined. Soil moisture was adjusted to −33 kPa and 14C‐ and analytical‐grade imidacloprid added to the soil at a rate of 1.0 mg kg−1. Imidacloprid‐spiked soils were incubated at 25°C for 16 wk. Replicate soil samples were periodically extracted successively with 0.01 M CaCl2, acetonitrile, and 1 M HCI. Sorption, as indicated by the sorption coefficient (Kd) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
69
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 0 publications
12
69
1
Order By: Relevance
“…However, variability in K OC sor values for the soils of different type and characteristics, and even for the soils with the same content of organic matter, indicated that not only organic matter content, but also its structure, aromaticity and polarity, affected the distribution of pesticide molecules in the soil/water system (Schwarzenbach et al, 2002). The values of K OC sor coefficient for IMI in the tested soils varied from 172 to 305 L/kg (Table 3), and they are consistent with reported K OC sor values (Cox et al, 1998b;Krohn & Hellpointner, 2002), especially for soils with similar textural characteristics. Estimated values of our study prove that, according to the McCall classification for the mobility of pesticides (McCall et al, 1980), IMI can be categorized as having a medium mobility (K OC sor 150 -500 L/kg) (Comfort et al, 1994), showing less tendency to be sorbed by the examined soils.…”
Section: Sorption Equilibrium Studysupporting
confidence: 87%
See 3 more Smart Citations
“…However, variability in K OC sor values for the soils of different type and characteristics, and even for the soils with the same content of organic matter, indicated that not only organic matter content, but also its structure, aromaticity and polarity, affected the distribution of pesticide molecules in the soil/water system (Schwarzenbach et al, 2002). The values of K OC sor coefficient for IMI in the tested soils varied from 172 to 305 L/kg (Table 3), and they are consistent with reported K OC sor values (Cox et al, 1998b;Krohn & Hellpointner, 2002), especially for soils with similar textural characteristics. Estimated values of our study prove that, according to the McCall classification for the mobility of pesticides (McCall et al, 1980), IMI can be categorized as having a medium mobility (K OC sor 150 -500 L/kg) (Comfort et al, 1994), showing less tendency to be sorbed by the examined soils.…”
Section: Sorption Equilibrium Studysupporting
confidence: 87%
“…Among the processes that determine the behavior and fate of pesticides in the soil/water environment, sorption-desorption and degradation processes are the key processes affecting pesticide persistence, transport and bioavailability determining the amount of pesticide that can reach the target organism and that can be volatilized, or leached. Information regarding the sorption and desorption characteristics of IMI are essential for predicting its fate within the soil environment (Cox et al, 1998a;Cox et al, 1998b;Cox et al, 2001;Fernandez-Bayo et al, 2007;Liu et al, 2006;Ping et al, 2010). Capri et al (2001) and Cox et al (1998c) investigated the effect of selected soil properties on the sorption of IMI using the batch equilibrium technique.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the reduction of C water in soils caused by soil aging was larger than that of C total . Several studies reported that soil sorption of pesticides such as imidacloprid, 26,27) nicosulfuron, 28) and simazine 29) increased during the aging period; thus, it is implied that the dissipation of C water is affected not only by general dissipation factors such as biodegradation, hydrolysis, and volatilization, but also by increasing soil sorption with increased aging time.…”
Section: Fig 2 Linear Regression Analysis Between Pesticide Concentmentioning
confidence: 99%